Influence of University Orientation on Fresh Students' Academic Attainment: A Case Study of Kabale University. - Nuwagaba, Melon (Kabale University, 2024)
This study examined the impact of Kabale University's orientation program on students’ academic attainment, integration into the university community, and peer mentorship effectiveness. Data collected from university students of varying academic years shed light on participation levels, perceived integration, academic performance, program customization, and peer mentorship experiences. Findings reveal varying degrees of participation, generally positive perceived integration, mixed results regarding academic performance influence, and diverse feedback on peer mentorship effectiveness. The study underscores the need for ongoing evaluation and refinement of the orientation program to address the multifaceted needs of students effectively. Further research avenues include longitudinal analysis of program impact, comparative studies of orientation programs, and exploration of peer mentorship dynamics for enhanced student support and academic success.